Angle Antenna Arrays of Travelling Wave with Central Excitation - Gorobets, N. N.; Gorobets, Yu. N.; Dakhov, V. M. (Видавничий дім «Академперіодика», 2013)
Angle Antenna Arrays of Travelling Wave with Central Excitation